A Critical Paradox: The Politics of an Urban Community-Based Nonprofit In Expanding Educational Opportunities to Underserved Youth. Issue 2 (3rd April 2019) - Sampson, Carrie; Overholser, Amber; Gatti Schafer, Josie
ABSTRACT: Nonprofit community-based organizations (CBOs) increasingly provide services that are traditionally thought to be a governmental responsibility. Through a qualitative case study, we examine the role, politics, and sustainability of a nonprofit CBO aimed at expanding opportunities for underserved youth. Our findings explain how this CBO worked to diligently meet these youth's needs and filled a gap resulting from the state and district's negligence within, and largely resulting from, neoliberal education reforms. Findings also point to a critical paradox that reflects the pressure for CBOs to subscribe to neoliberal practices. Study implications include the need for greater connection between public education and community partners.